Analisis tentang Dimensi-Dimensi Gaya Belajar Konsumen - Djatmika, Ery Tri; Murwani, F. Danardana (Jurnal Manajemen Akuntansi dan Bisnis, 2008)
Consumerâs buying decision and learning are two variables that are not separate. As a learner, consumer makes knowledge construction to reach meaningful learning, i.e. consumer solves the problem and makes buying decision correctly. Consumer varies in making knowledge construction. The variation is based on consumerâs learning style. This paper is reviewing the dimensions of consumerâs learning style based on the available learning style models. The review is intended to provide theoretical foundation to conduct research in the future. Keywords: consumerâs learning style, dimensions.